2020
DOI: 10.3389/fmicb.2020.00485
|View full text |Cite
|
Sign up to set email alerts
|

From Maternal Grazing to Barn Feeding During Pre-weaning Period: Altered Gastrointestinal Microbiota Contributes to Change the Development and Function of the Rumen and Intestine of Yak Calves

Abstract: Understanding the altered gastrointestinal microbiota is important to illuminate effects of maternal grazing (MG: maternally nursed and grazed) and barn feeding (BF: supplied milk replacer, starter feed, and alfalfa hay) on the performance and immune function of yak calves. Compared with the MG group, the significantly increased body weight, body height, body length, chest girth, and organ development of liver, spleen, and thymus were identified in the BF group, which were resulted from the significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 75 publications
3
32
0
Order By: Relevance
“…In addition to variations of yak rumen microbiomes, VFAs exhibited remarkable fluctuations in response to altitude. VFAs are produced by rumen microorganisms fermenting plant cellulose and other carbohydrates, and play an essential role in ruminant growth and immunity [ 47 ]. VFAs formed in the rumen are largely absorbed across the host’s ruminal epithelium [ 9 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to variations of yak rumen microbiomes, VFAs exhibited remarkable fluctuations in response to altitude. VFAs are produced by rumen microorganisms fermenting plant cellulose and other carbohydrates, and play an essential role in ruminant growth and immunity [ 47 ]. VFAs formed in the rumen are largely absorbed across the host’s ruminal epithelium [ 9 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the relative abundance of the genus Sphingomonas , and several species (e.g., OTU587, OTU487, and OTU433) significantly declined in the ileal mucosal microbiota of the HG group compared with the CON group. Sphingomonas is a strictly aerobic commensal bacteria of the human and animal intestines, and existing evidence from studies suggests that Sphingomonas contributes to the degradation of several types of polysaccharides, such as cellulose ( Birkholz and Kronenberg, 2015 ; Cui et al, 2020 ). Moreover, Sphingomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial community in the GIT of mammalian animals has been increasingly identified as an important factor in animals' growth, health, and production performance (Holmes et al, 2012;Yeoman and White, 2014). The microflora in the GIT is an intricate micro-ecosystem, which mainly composes of ciliate protozoa, anaerobic fungi, archaea, and bacteria (Falony et al, 2016;Cui et al, 2020a). A previous study has found that the microbiota acted as an essential role in regulating homeostasis and nutritional metabolism of the host's GIT (Rey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%